PENGARUH NARSISME CEO, UKURAN DEWAN (KOMISARIS), DIREKTUR PEREMPUAN, KESULITAN KEUANGAN, DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PERUSAHAAN - Widijaya, Widijaya; Putra, Darma Pratama (Jurnal Riset Akuntansi Politala, 2025)
Examining the influence of CEO narcissism, board size (commissioners), the presence of female directors, financial distress, and company size on corporate tax avoidance is the purpose of this study, where 491 annual reports of companies listed on the IDX in 2018-2022 were analyzed. The data analysis process includes the use of descriptive statistics, hypothesis testing, F-test, and Adjusted R-squared test. The research findings show that there is no significant influence between CEO narcissism and board size (commissioners) on tax avoidance, invalidating the proposed hypothesis. On the other hand, the presence of female directors was shown to have no significant effect, indicating women's tendency to make careful decisions. In addition, no effect was found on financial distress and tax avoidance, meaning that companies with difficulties are more likely to follow strict tax rules. However, a significant effect was found on company size and tax avoidance, meaning that the opportunity for tax avoidance is greater for larger companies.